Hydrodynamic aspects of river confluence with different water densities - Lyubimova, Tat’yana Petrovna; Lepikhin, Anatoliy Pavlovich; Parshakova, Yanina Nikolayevna; Kolshanov, Vadim Yur’yevich; Gualtieri, Carlo; Lane, Stuart Nicholas; Roux, Bernard (Computational Continuum Mechanics, 2020)
The confluence of rivers is characterized by highly complex internal processes. The hydrodynamic aspects of river confluences have received a lot of attention in recent years. For modeling purposes, it is generally assumed that the water densities of the rivers under consideration are close, and the density effects associated with their difference are neglected. In this approximation, we have previously investigated the confluence of the Vishera and Kama rivers. However, in some cases, the temperatures or salinity of the waters of merging rivers can differ significantly, and thereby the hydrodynamic mechanisms of mixing change considerably. In this paper, we examine the specific features of river confluences with and without taking into account density effects and by comparing both real and simplified channel (river) geometries. Simulations show that, at the density Froude number ∼1 which is observed in the rivers under consideration at the difference in salt concentration ~0.3 g/L, the mixing characteristics of these flows significantly change when they merge. The denser waters of the Vishera river begin to move under the less mineralized waters of the Kama river. As the Froude number exceeds the critical value, a fundamental rearrangement of coherent transverse structures occurs. These effects are more pronounced for the simplified model channel configuration, since taking into account the bottom heterogeneity significantly enhances vertical mixing. Earlier, the phenomenon in which the denser flow moves under the less dense flow was discovered by the authors for the confluence of the Chusovaya and Sylva rivers located in the backwater from the Kama hydroelectric power station.
Keywords: river confluence; density stratification; computational experiment